In Vitro Evaluation of Prebiotic Potential of Red Ginger (Zingiber officinale var. rubrum) Rhizome Ethanol Extract on Lactobacillus acidophilus and Escherichia coli - Gumelar, Fadil Rido; Suarantika, Farendina; Rusdi, Bertha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Prebiotics, including carbohydrates and phenols, promote beneficial gut bacteria (probiotics). Red ginger (Zingiber officinale var. rubrum) rhizomes, rich in these compounds, have been traditionally used in medicine but their prebiotic potential remains unexplored. This study investigated the in vitro prebiotic effects of Z. officinale var. rubrum rhizomes on Lactobacillus acidophilus (beneficial) and Escherichia coli (opportunistic) bacteria. Prebiotic activity was assessed using a turbidimetric method, measuring bacterial growth via UV-Vis spectrophotometry at 600 nm. The prebiotic index and percentage inhibition were calculated to evaluate the impact on bacterial growth. Additionally, total phenol content was determined using the Folin-Ciocalteu method. Results indicate that Z. officinale var. rubrum rhizomes exhibit prebiotic properties, stimulating L. acidophilus growth (prebiotic index of 156.035 and percentage inhibition value of -153.128%) while inhibiting E. coli growth (54.343% inhibition). The rhizomes contained 31.15 mg GAE/g extract of total phenols and 23.55% carbohydrates. These findings suggest that Z. officinale var. rubrum rhizomes possess prebiotic potential, warranting further investigation for potential applications in gut health management.